2008
DOI: 10.1007/s00392-008-0678-1
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital cooling with hypothermia caps (PreCoCa): a feasibility study

Abstract: In summary we demonstrated that the prehospital use of hypothermia caps is a safe and effective procedure to start therapeutic hypothermia after cardiac arrest. This approach is rapidly available, inexpensive, non-invasive, easy to learn and applicable in almost any situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Though there is debate regarding this approach, induced and controlled hypothermia is still used as a management strategy for patients surviving cardiac arrest [62]. Bjelland et al showed that after therapeutic hypothermia the effect of clopidogrel is non-existent in the first day of treatment and during the third day the recovery in partial [63].…”
Section: Mechanisms For Anti-platelet Drugs Resistance In Critically mentioning
confidence: 99%
“…Though there is debate regarding this approach, induced and controlled hypothermia is still used as a management strategy for patients surviving cardiac arrest [62]. Bjelland et al showed that after therapeutic hypothermia the effect of clopidogrel is non-existent in the first day of treatment and during the third day the recovery in partial [63].…”
Section: Mechanisms For Anti-platelet Drugs Resistance In Critically mentioning
confidence: 99%
“…48 In two studies 69,70 with gel caps, both also in cardiac arrest, no adverse effects were found but the investigators commented on the ease and speed (< 30 seconds) with which the caps could be applied.…”
Section: Resultsmentioning
confidence: 99%
“…The idea to develop new devices for selective neuroprotective cooling of the brain parenchyma has already been published [12,[26][27][28][29][30][31][32]. In each of the studies, the device became more specific and smaller [33].…”
Section: Discussionmentioning
confidence: 99%